Settlement Arrangement based on Landslide Risk Analysis in Girirejo, Bantul, Yogyakarta - Sri Aminatun; Yunalia Muntafi (Universitas Sebelas Maret, 2020)
Located on a hilly topography with a steep slope, highlighted the importance of settlement arrangement based on a landslide risk assessment in Girirejo village, Imogiri, Bantul, Yogyakarta. This study aims to map landslides risk, identify houses in the landslide risk zone, and provide recommendations for settlement arrangements. The research begins with observation, interviews, and focus group discussion. Disaster risk mapping and analysis were carried out through weighting method based on Perka BNPB No.2 of 2012 concerning General Guidelines for Disaster Risk Assessment and a formula with parameters of hazard, vulnerability, and capacity. Results showed the medium to a high-level of landslide risk was dominated by northern and eastern parts of Girirejo (21 families in red-zone, 23 families in yellow-zone), while western and southern regions had a low landslide risk level. This research also provided a formulation of settlements concept for medium and high-risk areas by considering landslides risk analysis study.